Recent advances in wearable iontronic sensors for healthcare applications - Choi, Sung-Geun; Kang, Se-Hun; Lee, Ju-Yong; Park, Joo-Hyeon; Kang, Seung-Kyun (Frontiers in Bioengineering and Biotechnology, 2023)
Iontronic sensors have garnered significant attention as wearable sensors due to their exceptional mechanical performance and the ability to maintain electrical performance under various mechanical stimuli. Iontronic sensors can respond to stimuli like mechanical stimuli, humidity, and temperature, which has led to exploration of their potential as versatile sensors. Here, a comprehensive review of the recent researches and developments on several types of iontronic sensors (e.g., pressure, strain, humidity, temperature, and multi-modal sensors), in terms of their sensing principles, constituent materials, and their healthcare-related applications is provided. The strategies for improving the sensing performance and environmental stability of iontronic sensors through various innovative ionic materials and structural designs are reviewed. This review also provides the healthcare applications of iontronic sensors that have gained increased feasibility and broader applicability due to the improved sensing performance. Lastly, outlook section discusses the current challenges and the future direction in terms of the applicability of the iontronic sensors to the healthcare.